2018
DOI: 10.1177/1553350618800078
|View full text |Cite
|
Sign up to set email alerts
|

Insights From Pupil Size to Mental Workload of Surgical Residents: Feasibility of an Educational Computer-Based Surgical Simulation Environment (ECE) Considering the Hand Condition

Abstract: The advantage of simulation environments is that they present various insights into real situations, where experimental research opportunities are very limited-for example, in endoscopic surgery. These operations require simultaneous use of both hands. For this reason, surgical residents need to develop several motor skills, such as eye-hand coordination and left-right hand coordination. While performing these tasks, the hand condition (dominant, nondominant, both hands) creates different degrees of mental wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…In all, our results could not replicate seminal laboratory work on pupillometry (cf., Beatty & Kahneman, 1966;Hess & Polt, 1960;Kahneman et al, 1969; or more recently, Moyes, Sari-sarraf, & Gilbert, 2019) and highlights the challenges in reaching external validity. Research on driving (cf., Recarte & Nunes, 2003), air traffic control (cf., Ahlstrom & Friedman-berg, 2006) and, for instance, piloting (cf., Causse et al, 2016) and surgery performance (cf., Dalveren et al, 2018;Erridge et al, 2017) already made great strides in closing this gap. While being seated and at a predominantly stable distance to experimental the stimuli, pupillometry in these contexts might become robust as soon as, i.a., variations in luminance (Lohani, Payne, & Strayer, 2019) and curvilinear effects can be accounted for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, our results could not replicate seminal laboratory work on pupillometry (cf., Beatty & Kahneman, 1966;Hess & Polt, 1960;Kahneman et al, 1969; or more recently, Moyes, Sari-sarraf, & Gilbert, 2019) and highlights the challenges in reaching external validity. Research on driving (cf., Recarte & Nunes, 2003), air traffic control (cf., Ahlstrom & Friedman-berg, 2006) and, for instance, piloting (cf., Causse et al, 2016) and surgery performance (cf., Dalveren et al, 2018;Erridge et al, 2017) already made great strides in closing this gap. While being seated and at a predominantly stable distance to experimental the stimuli, pupillometry in these contexts might become robust as soon as, i.a., variations in luminance (Lohani, Payne, & Strayer, 2019) and curvilinear effects can be accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…(2018) observed a pupil size decrease throughout a LEGO building process, except when the child participants had to back-step. Finally, differences between experts and non-experts in surgical skill have been related to pupil size (Erridge, Ashraf, Purkayastha, Darzi, & Sodergren, 2017;Richstone et al, 2010) and also harder visual-motor aiming tasks (such as with a one-handed grasper in endoscopic surgery) yield higher pupil dilation (Jiang, Zheng, Bednarik, & Atkins, 2015; see also, Dalveren, Cagiltay, Ozcelik, & Maras, 2018).…”
Section: Pupillometrymentioning
confidence: 99%
“…Other studies also showed the presence of a relation between attention and eye movements Rizzolatti, Riggio, Dascola, & Umiltá, 1987). According to an earlier study in which surgical tasks were performed under different hand conditions (both hands, dominant hand or non-dominant hand), there were changes in the pupil sizes of the surgical residents, indicating that when tasks were performed under the both-hands condition, they were considered more difficult than the dominant and nondominant hand conditions (Menekse Dalveren, Cagiltay, Ozcelik, & Maras, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…In Ref. 20 , the authors used pupil size as a metric for mental workload when comparing bimanual and unimanual performance during a simulated endoscopic task.…”
Section: Introductionmentioning
confidence: 99%